The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s1516-35982008000900008
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho reprodutivo, características do pelame e taxa de sudação em vacas da raça Braford

Abstract: RESUMO -Foram investigados os efeitos das características do pelame e da taxa de sudação (TS) sobre o intervalo de partos (IEP, n = 423) e os dias para o parto (DPP, n = 1.202) de vacas da raça Braford criadas em sistema extensivo em região tropical úmida no Mato Grosso do Sul, Brasil. As análises foram realizadas pelo método dos quadrados mínimos considerando para intervalo de partos os seguintes efeitos das classes de idade da vaca ao parto: grupo genético; pai; e regressão sobre a refletância da superfície … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…By contrast, when the animals had coat traits that makes heat loss difficult, such as longer hair and higher hair density, these animals tended to reduce T 4 hormone concentrations to reduce heat production (Table 2), probably due to the difficulty in dissipating heat through evaporative skin thermolysis (Maia et al , 2009). Bertipaglia et al (2008) found a relationship between coat traits and reproductive indices, in which the animals that had short HL showed shorter calving intervals. However, this response does not increase lineally over the environmental conditions imposed on the groups.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…By contrast, when the animals had coat traits that makes heat loss difficult, such as longer hair and higher hair density, these animals tended to reduce T 4 hormone concentrations to reduce heat production (Table 2), probably due to the difficulty in dissipating heat through evaporative skin thermolysis (Maia et al , 2009). Bertipaglia et al (2008) found a relationship between coat traits and reproductive indices, in which the animals that had short HL showed shorter calving intervals. However, this response does not increase lineally over the environmental conditions imposed on the groups.…”
Section: Resultsmentioning
confidence: 96%
“…This protection differs according to many factors such as coat thickness (CT) and hair characteristics (Silva 2008;Maia et al 2009). Substantial research has been conducted to analyse the relationship between coat characteristics and livestock productivity and other traits that are not directly related to thermoregulation (Bertipaglia et al 2007(Bertipaglia et al , 2008. McManus et al (2009), analysing five sheep groups, found that animals that showed lower respiratory rate (RR), rectal temperature (RT) and heart rate are characterized by better coat traits to heat adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prayaga and Henshall (2005) reported permanent environmental variance as a fraction of the phenotypic variance to be 0.19 for rectal temperature and 0.08 for coat score. Estimates of heritability for a variety of coat/hair characteristics ranged from 0.08 (number of hairs per cm 2 ) to 0.3 (measure of reflectance) in Braford cows (Bertipaglia et al, 2008). An estimate for heritability for the condition of the coat (subjectively scored as shiny, dull, or very dull) in dairy cows was 0.05 (Jørgensen et al, 2010).…”
Section: Estimates Of Genetic Effectsmentioning
confidence: 99%
“…On the other hand, the heritability for milk production at 305 days was estimated at 0.27 by Freitas et al (2000). Bertipaglia et al (2008) reported almost zero heritability to the interval between partum and days for calving. The relatively minor role of genetics and the largest domain of non-genetic factors on reproductive phenotype was reported by Silva et al (1998) whose results of heritability estimates were 0.35 for milk production in the first lactation and 0.05 for age at first calving.…”
Section: Introductionmentioning
confidence: 98%